FINANCIAL RETURN ON ASSETS. THE IMPACT OF THE FINANCIAL RETURN ON ASSETS OVER THE COMPANY’S DEVELOPMENT - Constantin Căruntu; Lăpăduşi Mihaela Loredana (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2009)
The financial rate of return is a significant indicator for assessing the economic and financial performance of an enterprise for the internal diagnosis, as well as for the analysis required by the external partners. The financial return is a basic indicator which characterizes the business performances that is found directly under the trade policy (trade cost), efficiency of capital employed (economic profitability) but also under the financial policy of the company. If the economic rate of return expresses a remuneration of the employed capital only in relation to operating activities, the financial rate of return quantifies a remuneration of the private capital trough all three types of activity: operational, financial and extraordinary. Starting from the consideration that the financial rate of return expresses the efficiency of equity or permanent capital use of the company we can state that it is of particular importance to the shareholders of the company, which considers according to it’s level whether their investments are justified and they will continue to support the business development through raising of fresh capital or abandonment for a limited period to one part of the dividends due. Managers, in turn, will be keen on maintaining an appropriate level of this rate, in order to retain their positions and to achieve the performance criteria of the company.